PERKEMBANGAN REMAJA AWAL, MENENGAH DAN IMPLIKASINYA TERHADAP PENDIDIKAN - Suryana, Ermis; Hasdikurniati, Amrina Ika; Harmayanti, Ayu Alawiya; Harto, Kasinyo (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This research investigates and assesses the task development, physical, intellectual, emotional, social, moral, and religious development, and educational effect of early and middle-aged teenagers. Adolescence is a transitory period between childhood and adulthood; the body seems “mature”, but when treatea as adults, early and middle adolescence fail to demonstrate maturity. Physical, intellectual, emotional, social, moral, and religious adaptations to change make this an extremely sensitive stage. The teenage era covered in this article is for early and middle adolescence. This is an example of library research. In addition to books, researchers consult publications and websites about the topics being investigated. Researches also employ qualitative methodologies based on observed occurrences and scientific reasoning. According to the findings of this study, early adolescent girls are still interested by the changes that occur in their own bodies; teenagers may develop new ideas and rapidly become attracted to the opposite sex. Teenagers in their twenties really crave friends, and teenagers in this age bracket are egotistical. Understanding early and middle adolescent development can help instrustors better understand their students and help them attain their full potential.